(untitled) (SCIENCE TIME JOURNAL, 2026)
This study explores gender differences in speaking skill development among Uzbek EFL university students through an online survey. Results reveal strong links between confidence, motivation, strategy use, and classroom participation. Female students demonstrate higher communicative engagement, while male students show lower strategic involvement, highlighting the need for differentiated speaking instruction.